Effect of mass-bathing on water quality of Brahma Sarovar (Kurukshetra) during solar eclipse, September 1987 (Assessment and development study of river basin series ;, 1988)
Study conducted during the peak bathing time, between 5.30 A.M. to 9.00 A.M. on solar eclipse day, September 23, 1987.